Registration of 'Canggu 5' Foxtail Millet. Issue 3 (24th June 2016) - Tian, Bohong; Zhang, Lixin; Liu, Yanli
Abstract : Summer foxtail millet [ Setaria italica (L.) Beauv.] is widely grown in the northern part of China, especially in Hebei Province, where it accounts for one‐fourth of the country's producing areas. A winter wheat ( Triticum aestivum L.)–summer foxtail millet–winter wheat rotation is a typical practice, so early maturity of foxtail millet is critical in this system. The objective of this research was to develop a summer foxtail millet cultivar with early maturity and promising agronomical performance. 'Canggu 5' (Reg. No. CV‐1, PI 676976) summer foxtail millet was developed from the cross Ji 8787/Shui 2, which was made in 1999 and released in December 2013 by Cangzhou Academy of Agricultural and Forestry Sciences (Certificate no. 2013001). Canggu 5 was assessed in multi‐environment replicated plots in the Northern China Summer Foxtail Millet Regional trials (NCSFMRT) from 2011 to 2013. Canggu 5 was 3 d earlier in maturity than the control cultivar Jigu 19. Canggu 5 was moderately resistant to stem lodging, which was similar to Jigu 19. Grain yields were consistently better than Jigu 19. The end‐use quality was equal or better than Jigu 19. Canggu 5 is an early maturing cultivar and is agronomically competitive in the summer foxtail millet production regions in northern China.